2018
DOI: 10.1507/endocrj.ej18-0166
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Hashimoto’s thyroiditis and its relationship with thyroid function and inflammatory status

Abstract: Several studies have shown the correlation between vitamin D [25(OH)D] deficiency and thyroid autoimmunity and reducing of thyroid autoantibodies in patients with normal levels of vitamin D combining with thyroid hormone replacement. However, other authors not agree with this association. It is still unclear whether the low 25(OH)D levels are the result of HT disease or a part of its cause. We studied 88 patients with HT regarding vitamin D status and thyroid autoimmunity markers as well as the relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 43 publications
5
43
0
4
Order By: Relevance
“…Linear regression analysis showed that 25(OH)D increased by 1 ng/ml at the normal reference level, with an increase of 2.78 ng/dl in FT4 concentration and a decrease of 0.17 mIU/L in TSH. A study (18) found that the decrease of FT4 level is a predictor of vitamin D deficiency in HT patients, which is consistent with our findings, suggesting that thyroid hormone can play a role in regulating the autoimmune function of the thyroid when vitamin D is sufficient. Our study found a positive correlation between FT4 levels and 25(OH)D levels, suggesting that vitamin D supplementation or thyroid hormones may be used to regulate the balance between FT4 levels and 25(OH)D.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Linear regression analysis showed that 25(OH)D increased by 1 ng/ml at the normal reference level, with an increase of 2.78 ng/dl in FT4 concentration and a decrease of 0.17 mIU/L in TSH. A study (18) found that the decrease of FT4 level is a predictor of vitamin D deficiency in HT patients, which is consistent with our findings, suggesting that thyroid hormone can play a role in regulating the autoimmune function of the thyroid when vitamin D is sufficient. Our study found a positive correlation between FT4 levels and 25(OH)D levels, suggesting that vitamin D supplementation or thyroid hormones may be used to regulate the balance between FT4 levels and 25(OH)D.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in recent years have shown that the association between HT and vitamin D remains controversial. Recent studies have found no effect on vitamin D levels in the HT group compared with the control group (18). Another researcher suggested that vitamin D was not involved in the early stages of HT (19).…”
Section: Discussionmentioning
confidence: 98%
“…Botello et al studied 88 patients with long-term HT and found a positive correlation between 25(OH)D levels, fT4, and (contrary to expectations) Th17 and TNFα. The authors hypothesized that low levels of fT4 are predictors of a deficiency of 25(OH)D and that the long evolution of the disease and treatment of hypothyroidism are related to a decrease in cytotoxic immune response, regardless of the levels of 25(OH)D [112]. The coexistence of AITD with other AID, such as celiac disease, also deserves consideration.…”
Section: What Is the Nature Of The Relationship Between Vitamin D Levmentioning
confidence: 99%
“…A total of 21 studies involving more than 3890 patients with AITD have been published till date evaluating the relationship between Vitamin D status and severity of thyroid autoimmunity as evaluated by autoantibody titers. [1819202122232425262728293031323334] These studies are often limited by small number of patients, different criteria used for defining Vitamin D deficiency/insufficiency and different criteria for AITD. Studies with more than 100 patients/controls have been elaborated in Table 1.…”
Section: Resultsmentioning
confidence: 99%